Potensi ekstrak daun pare (momordica charantia l.) sebagai alternatif meningkatkan kualitas hidup penderita Hepatitis B - Rahmatullah, Widia; Sari, Ana Dewi Lukita (Universitas Jenderal Achmad Yani Yogyakarta, 2021)
Background: Hepatitis is a desease that can be transmitted through blood transfussion. Treatment for this infectious desease can be done with antibotics or chemotherapy. The use of other herbal can also minimize the negative impact of using chemical products. The research needs to be used as hepatitis drugs. According to previous research it was stated that pare (Momordica charantia L.) leaves showed hepatoprotective ability. Objective: to determine the potential of bitter melon leaf extract (Momordica charantia L.) in treating hepatitis B. Methods: This study is used completely randomized design with three treatments. Each of the six replications was treated as follows, normal control, positif control (giving parasetamol dosis 750 mg/kg BB rats. Giving extract pare leaves (dosis 100 mg/kg BB rats). Results: The results of the one-way ANOVA test (Oneway Anova) SGOT and SGPT showed that there was a very significant effect between the treatment of bitter melon leaf extract on the levels of SGOT in rats with a significance value of 0.000. Conclusion: The observation parameters are measurement of leaves SGOT and SGPT. The results showed that pare leaf extract has the potential as a hepatoprotector. It isi hoped that this research can provide information add insight into science to utilize plants as herbal medicine.